BRCA1 and BRCA2 pathogenic sequence variants in women of African origin or ancestry. Issue 10 (3rd July 2019) - Friebel, Tara M.; Andrulis, Irene L.; Balmaña, Judith; Blanco, Amie M.; Couch, Fergus J.; Daly, Mary B.; Domchek, Susan M.; Easton, Douglas F.; Foulkes, William D.; Ganz, Patricia A.; Garber, Judy; Glendon, Gord; et al.
Abstract: BRCA1 and BRCA2 ( BRCA1/2 ) pathogenic sequence variants (PSVs) confer elevated risks of multiple cancers. However, most BRCA1/2 PSVs reports focus on European ancestry individuals. Knowledge of the PSV distribution in African descent individuals is poorly understood. We undertook a systematic review of the published literature and publicly available databases reporting BRCA1/2 PSVs also accessed the Consortium of Investigators of Modifiers of BRCA1/2 (CIMBA) database to identify African or African descent individuals. Using these data, we inferred which of the BRCA PSVs were likely to be of African continental origin. Of the 43, 817 BRCA1/2 PSV carriers in the CIMBA database, 469 (1%) were of African descent. Additional African descent individuals were identified in public databases ( n = 291) and the literature ( n = 601). We identified 164 unique BRCA1 and 173 unique BRCA2 PSVs in individuals of African ancestry. Of these, 83 BRCA1 and 91 BRCA2 PSVs are of likely or possible African origin. We observed numerous differences in the distribution of PSV type and function in African origin versus non‐African origin PSVs. Research in populations of African ancestry with BRCA1/2 PSVs is needed to provide the information needed for clinical management and decision‐making in African descent individuals worldwide.